On Subjectivity: estratégia de tradução e ativação de arquivos - Steen, Paula Alzugaray Van (2012)
As its object of investigation, this research looks at the project On Subjectivity, by Spanish artist Antoni Muntadas, for its representativeness of core strategies of contemporary art and communication. The text discusses how this work, conceived in 1978, articulates concepts as the reissue of information appropriated from media circuits; activation of archives; problematization of memory; the formation of collective memories; aspiration of artistic praxis networks; translation. The research works with the hypothesis that On Subjectivity, as a way of investigating multiple readings of journalistic images, is a work of open and participatory structure that favours its translation into contexts of Brazilian photojournalism and social networks on the Internet. Therefore, the translation of the work becomes a strategy for analyzing paradigm changes that occurred between the context of mail art networks and social networking sites, and between the practices of an archivist art and the database aesthetics